2017
DOI: 10.3847/1538-4357/aa890a
|View full text |Cite
|
Sign up to set email alerts
|

The Evaporation Valley in the Kepler Planets

Abstract: A new piece of evidence supporting the photoevaporation-driven evolution model for low-mass, close-in exoplanets was recently presented by the California-Kepler-Survey. The radius distribution of the Kepler planets is shown to be bimodal, with a "valley' separating two peaks at 1.3 and 2.6 R ⊕ . Such an "evaporation-valley' had been predicted by numerical models previously. Here, we develop a minimal model to demonstrate that this valley results from the following fact: the timescale for envelope erosion is th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

57
805
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 764 publications
(866 citation statements)
references
References 95 publications
57
805
3
1
Order By: Relevance
“…They argued that the underlying astrophysical effect could be photoevaporation, whereby stellar incident flux strips a planet's H/He atmosphere if the atmosphere is not thick enough, leaving a population of stripped, rocky planets and an untouched population of larger, gaseous mini-Neptunes (Owen & Wu 2013;Lopez & Rice 2016;Owen & Wu 2017;Van Eylen et al 2017). As an alternative hypothesis, they also suggested that gas accretion could be delayed during planet formation until the protoplanetary disk is already gas poor, creating a population of small, rocky planets (Lee et al 2014;Lee & Chiang 2016).…”
Section: The Planet Radius Distributionmentioning
confidence: 99%
“…They argued that the underlying astrophysical effect could be photoevaporation, whereby stellar incident flux strips a planet's H/He atmosphere if the atmosphere is not thick enough, leaving a population of stripped, rocky planets and an untouched population of larger, gaseous mini-Neptunes (Owen & Wu 2013;Lopez & Rice 2016;Owen & Wu 2017;Van Eylen et al 2017). As an alternative hypothesis, they also suggested that gas accretion could be delayed during planet formation until the protoplanetary disk is already gas poor, creating a population of small, rocky planets (Lee et al 2014;Lee & Chiang 2016).…”
Section: The Planet Radius Distributionmentioning
confidence: 99%
“…Owen & Wu (2017) performed a population synthesis starting with 3-10M Å cores and a period distribution of df P d P log 1.9 µ , which is similar to the power law index presented in this work. They then gave the simulated planets a range of envelope fractions from 1% to 30% and tracked the radii of these planets as they were subjected to photo-evaporation.…”
Section: In Situ Formationmentioning
confidence: 99%
“…They then gave the simulated planets a range of envelope fractions from 1% to 30% and tracked the radii of these planets as they were subjected to photo-evaporation. The Owen & Wu (2017) simulations produced very few sub-Neptunes with P 10 days < . In the Lee & Chiang (2017) model, hot super-Earth/ sub-Neptune occurrence rates are set by stellar rotation on the pre-main sequence.…”
Section: In Situ Formationmentioning
confidence: 99%
“…During this short lived phase, the planet rapidly cools and contracts, losing a substantial fraction of its gaseous envelope before the planetary atmosphere settles into a more stable configuration and continues to evolve on slower timescales (e.g. Jin et al 2014;Fossati et al 2017;Jin & Mordasini 2017;Owen & Wu 2017). For planets close enough to the host star, the atmosphere may then go through a long phase of efficient hydrodynamic escape, or even "blow-off", which, depending on the the planet's atmosphere mass, may or may not significantly affect the planet (e.g.…”
Section: Introductionmentioning
confidence: 99%